2014
DOI: 10.1083/jcb.201308029
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear lamin stiffness is a barrier to 3D migration, but softness can limit survival

Abstract: Lamins impede 3D migration but also promote survival against migration-induced stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
537
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 535 publications
(587 citation statements)
references
References 60 publications
35
537
7
Order By: Relevance
“…The nuclear lamina has likely evolved to protect the genome and enhance cell viability. Deep knockdown of lamin-A followed by constricted migration in our previous studies 5 indeed resulted in enhanced cell death by mechanism(s) consistent with DNA damage.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…The nuclear lamina has likely evolved to protect the genome and enhance cell viability. Deep knockdown of lamin-A followed by constricted migration in our previous studies 5 indeed resulted in enhanced cell death by mechanism(s) consistent with DNA damage.…”
Section: Introductionsupporting
confidence: 62%
“…However, at the bottom of Transwell membranes with highly constrictive micro-pores (3 µm diameter pores) 5 , migration causes damage to both repair of DSBs caused by ionizing radiation. Nuclear blebs with compromised lamina structure are also observed in cells expressing low levels of GFP-Lamin-A…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Confined migration causes increased nuclear envelope rupture While earlier studies were limited to cells in 2D culture, researchers have recently begun to investigate the role of the nucleus in 3D cell migration and uncovered that nuclear deformation can become a rate-limiting factor during confined migration. [13][14][15][16][17][18] When cells encounter constrictions smaller than the nuclear cross section, the large and relatively rigid nucleus must deform substantially to pass through the available space. 13,14,19 Two recent studies found that the forces exerted on the nucleus during this process frequently rupture the NE.…”
Section: Introductionmentioning
confidence: 99%